Using Genetic Variants to Evaluate the Causal Effect of Plasma Phospholipid Fatty Acids on Breast Cancer and Prostate Cancer: A Mendelian Randomization Study - Yang, Ze; Li, Jingjia; Sun, Yandi; Qu, Zihao; Lin, Yindan; Zhang, Lihong; He, Qian; Jia, Xueyao; Ahmad, Mashaal; Zhang, Xueyun; Luo, Yan (Frontiers in Genetics, 2021)
Background: Observational studies indicate that phospholipid fatty acids (FAs) have an impact on the etiology in cancers, but the results are conflicting. We aimed to investigate the causal association of phospholipid FAs with breast cancer and prostate cancer. Method: Fourteen single nucleotide polymorphisms (SNPs) were selected as instrumental variables to predict the level of ten phospholipid FAs from genome-wide association studies (GWASs). We obtained the summary statistics for the latest and largest GWAS datasets for breast cancer (113,789 controls and 133,384 cases) and prostate cancer (61,106 controls and 79,148 cases) from the Breast Cancer Association Consortium (BCAC) and Prostate Cancer Association Group to Investigate Cancer Associated Alterations in the Genome (PRACTICAL) consortium. Two-sample Mendelian Randomization analysis was applied. Results: The results demonstrate that the 10 individual plasma phospholipid FAs are not significantly associated with breast cancer risk and prostate cancer risk. Conclusion: The evidence is insufficient to support the causal association of the 10 individual plasma phospholipid FAs with breast cancer and prostate cancer.